2003
DOI: 10.5713/ajas.2003.1749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Level of Feeding on the Performance of Crossbred Cows during Pre- and Post-partum Periods

Abstract: The study was undertaken to see the effect of elevated feeding during pre-partum or pre-as well as post-partum period on the productive and reproductive performance of crossbred cows. The experiment lasted for 60 d pre-partum to 120 d post-partum. Eighteen dry pregnant crossbred cows divided into three equal groups were fed either as per NRC feeding standard (C) or 20% above NRC during 60 d pre-partum (T 1 ) or fed 20% above NRC during both 60 d pre-partum to 120 d post-partum (T 2 ) period. During prepartum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The birth weight of calves was increased by 18.09 and 23.61 percent in treatment T 2 and T 3 group respectively. The result of this experiment regarding birth weight agreement with the findings of Kale (1984), Usmani andInskeep (1989), Chokhataridi (1995), Singh et al, (2003) and Das et al, (2007) reported that increased feeding of challenge feeds before calving increased average body weight of calves.…”
Section: Calf Birth Weight and Body Weight Gain Of Cowsupporting
confidence: 90%
“…The birth weight of calves was increased by 18.09 and 23.61 percent in treatment T 2 and T 3 group respectively. The result of this experiment regarding birth weight agreement with the findings of Kale (1984), Usmani andInskeep (1989), Chokhataridi (1995), Singh et al, (2003) and Das et al, (2007) reported that increased feeding of challenge feeds before calving increased average body weight of calves.…”
Section: Calf Birth Weight and Body Weight Gain Of Cowsupporting
confidence: 90%
“…Similarly, postcalving dietary strategy could also impact the milk components. Cows fed diet above NRC recommendation (NRC1989+20%) in pre and post-partum stage had higher milk fat, SNF and total solid (Singh et al, 2003), however, protein and lactose were not affected by treatments.…”
Section: Body Weight and Body Condition Scoresmentioning
confidence: 93%
“…2017;Zhang et al, 2015). The increasing nutrient density of the diet with the increasing ratio of concentrate from Low to High resulted in increased TDMI (Singh et al, 2003). Literature showed that increased density of the diet improves the palatability and therefore increase the DMI (Gaafar et al, 2009;Little et al, 2017).…”
Section: Dry Matter Intakementioning
confidence: 99%
See 1 more Smart Citation
“…(1993) [23] , Prasad and Tomer (1995) [18] , Keady et al (2001) [11] , Khan et al (2002a) [12] , Panigrahi et al (2005) [17] , Kamboj et al (2016) [10] , Prima et al (2018) [19] and Raval et al (2019) [20] who reported that calf birth weights were not significantly affected by plane of precalving nutrition. Contrary to these findings Corah et al (1975) [2] , Kroker and Cummins (1979) [13] , Kale (1984) [9] , Usmani and Inskeep (1989) [27] , Chokhataridi (1995) [1] , Singh et al (2003) [24] , Das et al (2007) [4] and Ojha et al (2015) [15] reported that increased feeding before calving increased average body weight of calves.…”
Section: Calf Birth Weightmentioning
confidence: 96%